Perfect Fluid Cosmological Model In Presence Of Electromagnetic Field: Properties of a non-static cylindrically symmetric cosmological model with an electromagnetic field (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In this paper, we have constructed a non-static cylindrically symmetric cosmological modelwhich is specially homogeneous non-degenerate Petrov type-I. the energy momentum tensor has beenassumed to be that of a perfect fluid with an electromagnetic field and the 4-current is either zero orspace-tike. Various physical and geometrical properties like pressure, density, scalar of expansion andshear etc have been found and discussed